Stakeholders' characteristics as correlates of their perception of strategies for reducing early pregnancy among secondary school student in delta south and central senatorial districts. (2013)
This study examined stakeholders' characteristics as correlates of their perception of strategies for reducing early pregnancy among secondary school students in Delta South and Central Senatorial Districts. The study adopted a correlation approach. A total of one thousand five hundred (1500) stakeholders were used for the study. A qustionnaire, Strategies for Reducing Early Pregnancy among Secondary School Students (SREPASSS) was used for data collection. The data obtained were analysed using descriptive, Analysis of Variance and multiple regressions. The findings of the study indicated that there is significant difference in perception in terms of occupation was a significant factor in explaining difference in the perception of stakeholders on strategies for reducing early pregnancy among secondary school students (F(5.1494) = 3.492,p≤0.05). Religious leaders had better perception than the traders while other groups did not differ significantly in their perception. Stakeholders characteristics jointly influenced their perception ( F (5.1494)= 3.037,p≤0.05) while marital status was then most influential factor. Based on the findings of this study, it was recommended that all stakeholders especially parents, school authorites and students should adopt and implement all identified strategies for reducing early pregnancy among secondary school students. Serious campaign should be mounted for traders and their wards to change their views on issues of sexuality.